2022
DOI: 10.3390/jcm11092562
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Gestational Age and Risk for Long Term Ophthalmic Morbidities among Offspring Delivered in Different Preterm Subgroups

Abstract: Objective: To investigate whether there is a linear association between the degree of prematurity and the risk for long-term ophthalmic morbidity among preterm infants. Study design: A population-based, retrospective cohort study, which included all singleton deliveries occurring between 1991 and 2014 at a single tertiary medical center. All infants were divided into four groups according to gestational age categories: extremely preterm births, very preterm births, moderate to late preterm births and term deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…We retrospectively collected preterm infants examined between June 2021 and June 2022. The inclusion criteria were birth weight ≤1500 g and very preterm birth[ 11 ] (gestational age, GA: 28–32 weeks), including ROP with a favorable outcome. Exclusion criteria included severe systemic disease of the mother and a history of anticipated drug use; premature infants with severe systemic disease; and eye diseases requiring treatment.…”
Section: Methodsmentioning
confidence: 99%
“…We retrospectively collected preterm infants examined between June 2021 and June 2022. The inclusion criteria were birth weight ≤1500 g and very preterm birth[ 11 ] (gestational age, GA: 28–32 weeks), including ROP with a favorable outcome. Exclusion criteria included severe systemic disease of the mother and a history of anticipated drug use; premature infants with severe systemic disease; and eye diseases requiring treatment.…”
Section: Methodsmentioning
confidence: 99%
“…These abnormalities include retinopathy of prematurity (ROP), strabismus, color vision deficits, visual field defects, decreased visual acuity and refractive error [5]. In a retrospective cohort study from the Soroka Univer-sity Medical Center (SUMC), rate of visual disturbances and retinopathy of prematurity (ROP) was significantly higher among the 24-28 gestational weeks group [6]. Kozeis et al [7] found preterm infants were associated with impairment of some aspects of visual function.…”
Section: Introductionmentioning
confidence: 99%
“…Preterm delivery (PTD: <37 gestational weeks) complicates 5–13% of deliveries worldwide [ 1 ], and is a leading cause of perinatal and childhood mortality and morbidity [ 2 , 3 , 4 , 5 ]. PTD is also a risk factor for long-term maternal health complications, including cardiovascular and renal morbidities [ 6 , 7 ].…”
mentioning
confidence: 99%
“…Fetal development occurs throughout the entire pregnancy until full term; therefore, when PTD occurs, the newborn is not physiologically and metabolically mature, leading to immediate and long-term complications [ 2 , 3 , 4 , 5 ]. The severity of these complications depends mainly on gestational age at delivery, and increases with reduced gestational age; this is reported by Gutvirtz et al [ 3 ] and Zer at al.…”
mentioning
confidence: 99%